2018
DOI: 10.1242/dev.153460
|View full text |Cite
|
Sign up to set email alerts
|

Precise spatial restriction of BMP signaling in developing joints is perturbed upon loss of embryo movement

Abstract: Dynamic mechanical loading of synovial joints is necessary for normal joint development, as evidenced in certain clinical conditions, congenital disorders and animal models where dynamic muscle contractions are reduced or absent. Although the importance of mechanical forces on joint development is unequivocal, little is known about the molecular mechanisms involved. Here, using chick and mouse embryos, we observed that molecular changes in expression of multiple genes analyzed in the absence of mechanical stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 43 publications
3
53
0
1
Order By: Relevance
“…Another striking aspect of the pattern is territories of reduced YAP in the sub‐chondral zone, proximal and distal to the shoulder and elbow joint. We have previously shown that territories of Wnt and BMP signalling are distinct and complimentary at rudiment termini with Wnt active in the joint and BMP in the sub‐chondral region and that this spatial organization of distinct signalling territories is lost under immobilization in both chick and mouse models . Here we show that distinct territories of YAP accumulation are also homogenized in the absence of movement.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Another striking aspect of the pattern is territories of reduced YAP in the sub‐chondral zone, proximal and distal to the shoulder and elbow joint. We have previously shown that territories of Wnt and BMP signalling are distinct and complimentary at rudiment termini with Wnt active in the joint and BMP in the sub‐chondral region and that this spatial organization of distinct signalling territories is lost under immobilization in both chick and mouse models . Here we show that distinct territories of YAP accumulation are also homogenized in the absence of movement.…”
Section: Discussionsupporting
confidence: 52%
“…We have previously used a comparative transcriptomics approach to show extensive alteration of gene expression in immobilized developing humeri and associated joints: Genes associated with Wnt signalling and other regulatory pathways were among the most sensitive to immobilization . We recently showed that Wnt and BMP signalling pathways are reciprocally regulated at the joint interface in response to movement . However, precisely how cells transduce physical stimuli to impact gene expression remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A further possibility for why some joint shapes were more abnormal in the reduced muscle group than in the muscleless group could be due to secretion of factors from the muscle (which would impact only on the reduced‐muscle group and not the muscleless group). Bone‐muscle crosstalk has been shown to be important for both bone and muscle (reviewed in Brotto and Bonewald) and it is possible that similar processes play a role in early cartilage development and cartilage morphogenesis …”
Section: Discussionmentioning
confidence: 99%
“…Fetal movements are important for the development of healthy joints and absent or abnormal fetal movements can lead to developmental skeletal abnormalities such as developmental dysplasia of the hip (DDH) and arthrogryposis . DDH is a condition in which the immature hip joint is unstable or dislocated, with an incidence of 1.3 per 1,000 live births .…”
mentioning
confidence: 99%
See 1 more Smart Citation